A contribution to the knowledge of corumbatai permian pelites geotechnical behaviour, Brazil - De Oliveira Campos, Jayme [UNESP]; Villar, Orencio Monge; Frazão, Ely Borges (My University, 2016)
Some sedimentary rocks may reveal compromising behavior in civil works,owing their peculiar response to weathering phenomena, related with their structural pattern associated to own physical genesis characteristics. The evidence of such effects has appointed to the need of geotechnical tests, in order to collect and to analyse the whole of their properties providing their nature, and aiding the interpretation of their behaviour in practice. Besides, the collected data will certainly be applied in future projects where similar rocks occur. The tests may lead to the specifications improvement, yet poorly in Brazil, suited the material in question.